Healthcare Professionals’ Attitudes towards Adverse Drug Reactions Reporting in Primary Healthcare Settings: A Cross-sectional Survey - Yuniar, Cindra Tri; Fadhilah, Rizka Zu; Anggadiredja, Kusnandar; Amalia, Lia (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Spontaneous Adverse Drug Reactions (ADRs) reporting is a key to improving the post-marketing safety of medicines. The important factor of under-reporting is lack of awareness for the purpose of ADRs monitoring and reporting. Spontaneous reporting is performed by the patients or consumer to the healthcare professionals and/or industry, then the healthcare facilities and industry should report the suspected ADRs to the National Agency of Drugs and Food Control (NADFC). To date, there is a lack information and study about attitudes on ADRs reporting by healthcare professionals (HCPs), especially in primary healthcare settings.Objectives: The aim of this study was to identify the attitudes towards ADRs reporting by healthcare professionals (HCP).Methods: This research was survey study with cross-sectional design, from November 2022-March 2023. The questionnaire, that have been validated and reliable, was distributed to 3 primary healthcare facilities. demographic data questions (6 items), experiences (3 items), knowledge (4 items), and motives for reporting (1 item).Results: Total 39 HCPs completed the survey, including 14 nurses, 9 midwifes, 3 general physicians, 3 pharmacists, and 10 other professions. Most of respondents were women (84.6%), and mostly the HCPs have been working for ≥5 years (74.3%). Among 39 respondents, only 1 pharmacist have a good attitude about ADRs reporting. The other HCPs had a lack of knowledge and safety awareness. The dominant motives for reporting the ADRs was serious or severe ADRs (39.4%) and the assurance of causality assessment by suspected drugs (15.4%).Conclusion: In conclusion, the HCPs in primary healthcare settings had poor attitudes towards ADRs reporting.